The Supremacy of European Union Law: An Inevitable Revolution or Federalism in Action? - Arigho, Redmond (Graduate Students’ Union of the University of Dublin, Trinity College, 2014)
The European Union is a fully fledged, sui generis legal order. The doctrine of supremacy, developed by the European Court of Justice in the seminal case of Costa v ENEL established Union laws having primacy over domestic law of the Member-States thereby rendering as non-applicable national law that was deemed to infringe EU Law. Although the ECJ has clarified that this extends to domestic constitutional law, this claim of authority has not been welcomed in its entirety in any of the Member-States. This issue is encapsulated in the so called ‘kompetenz-kompetenz’ debate, a phrase uttered by the German Constitutional court. According to the Member-States, they retain the ultimate authority to designate which law reigns supreme (regarding it as a fundamental component of national sovereignty) and most importantly, to what extent Union competence extends to. It is clear therefore that there is a fundamental dichotomy over the position claimed by Union law, and that of the Member-States. This has been described as eradicable conflict that must inevitably lead to conflict between the Union legal order and the national ones, with the outcome resulting in a legal revolution which will result in in one of two situations: (i) the acceptance on behalf of the Member-States of the Supremacy doctrine as enunciated by the ECJ or (ii) a clear rejection of the ECJ’s claim and the positioning of national constitutional law as the ‘grundnorm’ of domestic Member-State law. The aim of this paper is, however, to demonstrate that rather than an eradicable conflict, the current dichotomy between the two legal orders is a necessary result of federalism. Under this theory, the ‘conflict’ between the two systems will not necessarily lead to a legal revolution, and that in fact, such diametrically opposed claims from two sui generis legal orders within the one federal system are bound to occur in a federal legal order. Federalism, by its very nature, is the legal fruition of competing legal orders. It is proposed to undertake a comparative analysis of some of the seminal decisions throughout the EU on supremacy, from both the perspective of the Court of Justice and the most relevant emanating from national courts. A teleological analysis of these legal positions will then be undertaken within the competing frameworks of ‘conflict’ and ‘legal pluralism’. Ultimately, the position that legal federalism, by its very nature, engenders such a ‘conflict’ is proposed and defended.
Keywords: European Union law; domestic constitutional law; supremacy; conflict of legal orders